Sex and standard levels differences in anthropometric and physical fitness characteristics in youth handball players - Ortega-Becerra, Manuel; Pareja-Blanco, Fernando (2020)
This study analyzed the relationships between throwing velocity and anthropometric and fitness parameters in young female and male handball players of different ages. A total of 159 players participated: females under-16 (FU16, n=44) and under-14 (FU14, n=21); males under-16 (MU16, n=54) and under-14 (MU14, n=40). The following was measured: body height, arm span, body mass, total finger span, hand length, maximal isometric handgrip force, handball throwing velocity, 20-m sprints, countermovement jump, and change of direction. Group MU16 showed significantly (p<.05) greater values of anthropometric characteristics than groups FU16 and MU14. No significant differences were observed between FU14 and MU14 in any of the anthropometric variables analyzed, or between the two female groups (FU16 vs. FU14). MU16 showed significantly (p<.05) better performance in all fitness parameters than FU16 and MU14. No significant differences were observed between FU14 and MU14 or between FU16 and FU14. Throwing performance correlated (p<.05) with almost all the anthropometric and fitness parameters evaluated within each group. Taken together, male handball players showed greater anthropometric and fitness characteristics in the U16 compared to the U14, whereas no substantial differences were observed in female handball players between the two groups. Handball throwing velocity is associated with body and hand dimensions and other physical performance parameters.
Bibliografija: str. 240-241.
Summary.
Keywords: Rukometaši -- Spolne razlike -- Antropometrijske karakteristike -- Vertikalni skok -- Sprint -- Brzina bacanja